‘Locations of Possibility’: Critical perspectives on partnership - Cates, Rhiannon M.; Madigan, Mariah R.; Reitenauer, Vicki L. (International Journal for Students as Partners, 2018)
This article offers critical perspectives on collaborative partnerships and feminist teaching that revise paradigms of power, prioritize student agency, enrich curriculum and scholarship, and sustain empowered communities of learning that challenge institutional compartmentalization. The authors reflect on how co-created curriculum can catalyze new professional partnerships that in turn contribute to refreshed learning experiences and communities. This article presents evidence of how a partnership orientation effectively encompasses an ethic and practice of feminist teaching, posits a framework of feminist pedagogy and praxis into the discourse of partnership, and exemplifies possibilities of these practices as important steps towards a (re)vision of liberatory learning.